Migration, Environment and Climate Change in Yemen - International Organization for Migration (United Nations, 2025)
The Migration, Environment, and Climate Change (MECC) Country Report on Yemen by IOM explores the complex links between climate change, environmental degradation, and human mobility in Yemen. Given the country’s aridity, water scarcity, and vulnerability to climate-induced hazards—exacerbated by conflict—this study provides an evidence-based foundation for policy discussions and interventions. Utilizing qualitative mixed methods, including key informant interviews and focus group discussions, the report highlights how extreme weather events (floods, cyclones, wildfires, dust storms) and slow-onset environmental changes (drought, rising temperatures, soil degradation, and sea level rise) drive displacement, alter livelihoods, and exacerbate vulnerabilities. The findings underscore adaptive responses—such as makeshift repairs and community support—that remain insufficient amid Yemen’s humanitarian crisis. The report also examines migration dynamics, revealing how conflict, economic instability, and environmental degradation fuel internal displacement and migration through Yemen toward neighboring countries. Key challenges identified include governance gaps, resource scarcity, gender disparities, and deteriorating health and security conditions, making urgent policy action essential.